Development of Trafic Control Device for Road Construction - Kadis, Ghazali (Multidisciplinary Applied Research and Innovation, 2023)
Numerous workers and road users, particularly motorists and motorcyclists, are involved in road construction and upgrade projects. The potential of mishaps for the workers during this construction is very high. Similarly, drivers and riders ofmotorcycles. Labour is utilised to enforce traffic laws, and these workers are in grave danger. The effort to maintain safety and maintain a smooth flow of traffic on a road construction site requires the use of a traffic controller, also known as a flagman. A long time ago, a similar practice was introduced, and it has now become widespread. As a result, a product is suggested to manage traffic at this building site. Traffic lights are a necessary component of contemporary living. We can observe how the flow of traffic in our city is improving, with vehicles travelling faster between destinations. This is due to the fact that, in contrast to earlier times, the traffic situation is now managed by a highly advanced traffic signal management system. Traffic signals that do not require officers to stand guard at every vehicle route have already been developed by humans. With the traffic light system, every vehicle's travel on the road is more organised and systematic in accordance with its appropriate directions, which might reduce accidents.Different traffic signals are created and intended to be used not only to regulate the flow of traffic on the road but also to be employed in an emergency.